Increased Understanding and Role of the Community in Handling Waste in the Village of West Doom, Sorong Islands District - Roger Tabalessy; Ivonne M. Leiwakabessy; Dwi Indah Widya Yanti; Jean Anthoni; Melani Manurung; Melisa Masengi; Sarlota M.P Osok (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Increased settlement numbers and population development can trigger an increase in the amount of waste produced in the environment. The purpose of the activities carried out is to improve people's understanding of the importance of environmental cleanliness and their involvement in cleaning and maintaining the environment. The methods used in this devotion are methods of socialization and participation. With this method, we invite the public to understand and be involved in maintaining the cleanliness of the surrounding environment, both on land and in coastal areas. The results obtained by the community are quite enthusiastic and play an active role in these activities. It is hoped that the community is not only involved when there are joint activities with campuses and other institutions, but this can be a shared culture in the western village of catastrophe. Clean and healthy living is the key to a clean environment.